PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SOLVABILITAS, OPINI AUDIT DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ebang, Yohanes Baptista Tupen; Falah, Syaikhul; Pangayow, Bill J.C (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to analyze the effect of company size, profitability, solvency, audit opinion and the sizeÂ of the public accounting firm on audit delay in manufacturing companies listed on the Indonesia Stock Exchange. The analysis was carried out using multiple linear regression analysis, where the classicalÂ assumption test was carried out first, the analysis tool using SPSS 21. The observation period in thisÂ study was 2016-2018 using a sample of 36 selected manufacturing companies based on purposiveÂ sampling with a total of 108 samples overall during 3 years of observation. The results of this studyÂ indicate that the average audit delay in manufacturing companies in 2016-2018 is 78.28 days. TheÂ results showed that the variable size of the company, profitability, solvency, audit opinion and the sizeÂ of the public accounting firm did not affect audit delay. However, the independent variablesÂ simultaneously influence the dependent variable.